Handbook on the Albanian Collateral Law - Baranes, Yair; Cuming, Ronald C.C. (Washington, DC: World Bank and the International Finance Corporation, 2013)
On October 18, 1999, albania passed the Law for Securing Charges, which in many of its concepts and features has no precedent in prior Albanian law. This is a complex law, for it bears on the rights annd conduct of creditors, debtors, and a range of other persons who can be affected by securing charges, and it provides for a modern, computer-based registry system. This report provides a detailed explanation of the Law for Securing Charges as well as of related legislation. It concentrates on the issues central to the functioning of the new law, and because it is intended for a wide audience, it relies on no-technical language wherever possible. In addition, it pays special attention to the new terminology introduced by the Law for Securing Charges. The largest part of this report deals with the Law for Securing Charges and Regulations of Securing Charges. It begins with a description of the context in which the Law for Securing Charges functions and an overview of the basic concepts contained in the Law for Securing Charges. Part A presents the Law. Part B presents the revised Article 605 of the Civil Code. Part C provides the annotated Regulations of Securing Charges applicable to the Registry of Securing Charges. It also includes a short commentary on the Albanian Government decision limiting its liability for damages caused as a result of malfunctioning of the registry system. Appendix A details the instructions for completing registry notices and for obtaining searches.